The Teaching Satisfaction of an Academic Faculty and Phd Students - Metelski, Adam (Studia Oeconomica Posnaniensia, 2017)
Despite the fact that job satisfaction is an area that is very commonly researched, it still continues to fascinate. The purpose of this article is to present the results and conclusions of a study on teaching satisfaction of an academic faculty and PhD students, with a particular emphasis on their position at the university. The roles of an academic faculty cover several areas of activity (teaching, scientific and organizational), but this article focuses only on the activity of teaching. Whereas interest in job position stems from the fact, that it is one of the important factors that determines the level of employee satisfaction